DETERMINAN PRODUKTIVITAS PENGUSAHA RUMPUT LAUT PADA KETERBATASAN SALURAN PEMASARAN DI SENTRA PRODUKSI - Bahari Bahari; M. Arif Dirgantoro; Doddy Ismunandar Bahari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2012)
The research aimed to predict farmer’s productivity level and to identify factors affecting productivity level in seaweeds farming in Muna District Southeast Sulawesi. To achieve that objectives, frontier cost function using OLS and MLE estimation method with Cobb-Douglas functional assupmtion was used. Eighty six respondents were selected by proportional random method. The results of cost function based on OLS and estimation based on MLE showed that variables of seed prices, transportation prices, labor price and amount of production had jointly significant affect. Research showed farmers achieved productivity levels between 80 to 99 percent with an average of 96 percent. Productivity level distribution was influenced significantly by seaweed sales price and dummy of marketing channels. Important policy implication was to increase amount of production to fulfill market demand can only be done by increasing scale because gap between average productivity of farmers with maximum productivity rate of allocation and best combination of inputs (best practiced farm) is fairly narrow. Increasing scale of seaweed farmers must been followed with reforming that involving the government to correct the marketing system of seaweed so gave better impact on the price at farm level that would increase farmers productivity.